РОЛЬ АНГЛИЙСКОГО ЯЗЫКА В КОНТЕКСТЕ ПАТРИОТИЧЕСКОГО ВОСПИТАНИЯ - Менлимуратова, Э.А.; Турсынбаева, С.Р. (SCIENCE and SOCIETY, 2025)
The article examines patriotism as a special form of self-realization and social behavior of citizens, grounded in high moral and civic values. The author emphasizes that true patriotism is demonstrated through love for the homeland, willingness to serve the country, and a commitment to preserving the integrity. Special attention is given to civic responsibility, duty, and the pursuit of sustainable development as key indicators of patriotic consciousness. Thus, patriotism is presented not merely as an emotional feeling, but as an active life stance aimed at the welfare of society and the state.